Role of stationary and transient waves in CO2 supersaturation during northern winter in the Martian atmosphere revealed by MGS radio occultation measurements. Issue 5 (21st May 2017) - Noguchi, K.; Morii, Y.; Oda, N.; Kuroda, T.; Tellmann, S.; Pätzold, M.
Abstract: The Martian atmosphere, which mainly consists of carbon dioxide (CO2 ), is characterized by extremely low temperatures that cause CO2 gas to freeze and dry ice to form. To date, temperatures below the CO2 saturation temperature, which can be attributed to the effects of atmospheric waves, have been observed in the polar winter and in the mesosphere. Using data from Mars Global Surveyor (MGS) radio occultation measurements, we investigated the role of large‐scale atmospheric waves including stationary and transient waves at northern high latitudes in winter on CO2 supersaturation. A distinct longitudinal dependence of CO2 supersaturation was observed at altitudes higher than the pressure level of 200–400 Pa, where a stationary wave with a wave number of 2, whose temperature amplitude had minima at 30–100 Pa, lowered the background temperature to a level close to the CO2 saturation temperature. However, the stationary wave alone was not sufficient to cause CO2 supersaturation. Additional temperature disturbances caused by transient waves, namely, superposition of both waves, had a significant role in CO2 supersaturation. The longitudinal dependence of the occurrence of CO2 supersaturation revealed by our study might affect the longitudinal distribution of CO2 snowfall and the formation of the seasonal polar ice cap. Key Points: Using data from MGS radio occultation measurements, we studied the role of stationary and transient waves on CO2 supersaturation on Mars We found a longitudinal dependence of CO2 supersaturation above 200–400 Pa, where stationary waves lowered the background temperature However, additional disturbances by transient waves, namely, superposition of both waves, had a significant role in CO2 supersaturation